Fotodegradacja małocząsteczkowych WWA w warunkach reakcji Fentona = Fotodegradation of low mass molecule PAHS in fenton process - Kozak, Jolanta; Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Nowadays, the attention of many researchers and scientists is focused on wastewater treatment technologies which are designed to remove toxic and/or persistant compounds. PAHs belong to this type of compounds. Studies have shown that advanced oxidation processes (AOP-advanced oxidation processes) can be used for PAHs degradation. One of the AOP methods is oxidation using Fenton's reagent (Fe2+/H2O2).
Keywords: WWA; AOPs; reakcja foto-Fentona; ścieki koksownicze; oczyszczanie ścieków koksowniczych; photo-Fenton; coke wastewater; pretreated coking wastewater